Antibacterial activity of different biomass components of Cerbera odollam and their potential to be used as new preservative for wood based products - M. H. M. Amini; R. Hashim; N. S. Sulaiman; O. Sulaiman; S. F. Sulaiman; F. Abood; F. Kawamura; R. Wahab; M. Mohamed; M. S. M. Rasat (Trans Tech Publications, 2015)
Cerbera odollam’s tree parts were extracted with methanol and further fractionated using n-hexane, ethyl acetate and ethanol, followed by antibacterial assay against Bacillus subtilis, Bacillus licheniformis, Escherichia coli and Pseudomonas aeruginosa. Hexane soluble parts from flower, fruit, leaf, wood, bark and ethyl acetate soluble part from bark showed antibacterial activity against Bacillus subtilis. Hexane soluble parts from leaf and bark and ethyl acetate soluble parts from wood showed antibacterial activity against Bacillus licheniformis. All fractions appeared ineffective on Escherichia coli and Pseudomonas aeruginosa. Screened extracts were analysed using FTIR. Experiments were continued with impregnation of methanolic extracts of Cerbera odollam into Melamine-urea formaldehyde (MUF) particleboards, Phenol-resorcinol formaldehyde (PRF) particleboards and solid wood samples followed by exposure to wood-boring beetles and natural decaying.